A Scoping Review of Preferences of Men Who Experienced Sexual Assault: Implications for Adaptation of Trauma-Focused Cognitive Behavioral Therapies - Lydia Gamache; Laurence Dubé; Geneviève Belleville (American Journal of Men's Health)
About 1 in 10 men experiences sexual assault, resulting in various difficulties most frequently associated with post-traumatic stress disorder. However, trauma-focused cognitive behavioral therapies (TF-CBT) seem less effective for men who experienced sexual assault compared to women. Efficacy of TF-CBT could be improved by adapting interventions according to the empirical data detailing men’s preferences regarding psychological services. This scoping review aimed to document preferences of men who experienced sexual assault regarding psychological services, and to explore barriers and motivators to help-seeking for this population. A systematic approach was used to gather literature describing preferences regarding psychological services, and barriers and motivators to help-seeking. Thirty-five peer-reviewed studies and two non-peer reviewed reports met inclusion criteria. Data from included articles were extracted using a systematic extraction grid. A thematic content analysis was conducted to synthesize and present the results from the 37 studies. The number of empirical studies on preferences regarding psychological services was limited as only five documented preferences, all related to the clinician’s characteristics (e.g., clinician’s gender) and the type of intervention (e.g., action-oriented). Most studies reviewed barriers to help-seeking. The barriers most frequently identified were adherence to masculine norms and to myths about male sexual assault. Injury or substance abuse following sexual assault often act as motivators to help-seeking for men. To adapt TF-CBT to men who experienced sexual assault, researchers and clinicians should accommodate and further study these men’s preferences, consider their motivators regarding help-seeking and alleviate barriers to help-seeking, notably by deconstructing masculine norms.